PEMBENTUKAN PERDAGANGAN BEBAS ASEAN-CHINA (ASEAN-CHINA FREE TRADE AREA) DAN DAMPAKNYA BAGI PETANI DI INDONESIA - Indriastuti, Suyani (Universitas Wahid Hasyim, 2005)
Recently, free trade is a global phenomenon where the regions effort to make an exclusive free trade area. The Association of South East Asian Nations (ASEAN) and China signed a comprehensive economic partnership agreement on the teenth of ASEAN summit. The parties agreed to strenghthen their coorperation in many sectors which the one of that was agriculture sector. So Indonesian as ASEAN member has enthusiasm to apply this agreement. It has many impacts for Indonesian farmer.Key word : Free trade, agriculture,Indonesian farmer